2020
DOI: 10.1088/2399-6528/ab852e
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solutions for phase noise due to pointing jitter with the LISA telescope

Abstract: The aim of the Laser Interferometer Space Antenna (LISA) is to detect gravitational waves through a phase modulation in long (2.5 Mkm) laser light links between spacecraft. Among other noise sources to be addressed are the phase fluctuations caused by a possible angular jitter of the emitted beam. The present paper follows our preceding one (Vinet et al 2019 Class. Quant. Grav. 36, 205 003) based on an analytical study of the far field phase. We address here a numerical treatment of the phase, to first order i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Initial validation of the software was carried out by comparison to the Airy disk, an analytical solution that arises when a uniform amplitude fills a circular aperture and is propagated to a distance, z, in the far field [8]:…”
Section: Validation Of the Propagation Codementioning
confidence: 99%
See 1 more Smart Citation
“…Initial validation of the software was carried out by comparison to the Airy disk, an analytical solution that arises when a uniform amplitude fills a circular aperture and is propagated to a distance, z, in the far field [8]:…”
Section: Validation Of the Propagation Codementioning
confidence: 99%
“…A limitation of these methods is that, for higher order aberrations, the equations become unmanageable [8]. The method presented in this work therefore takes a numerical approach, validated extensively by comparison to known analytical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Vinet's research showed that the coupling of wavefront errors and pointing jitter noise can only be reduced through special processing of the telescope's optical system, indicating that achieving RMS wavefront distortion less than λ/500, which is currently beyond the capabilities of state-of-the-art technologies [2]. In recent years, researchers from various countries have conducted theoretical simulations on wavefront errors and pointing jitter noise in different gravitational wave detection backgrounds [6][7][8], and the research results generally impose stringent requirements on the wavefront imaging quality of telescopes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sasso et al extended this analysis by considering Gaussian profile, transmitting beam clipping and more terms of Zernike polynomials [10]. Vinet et al carried out theoretical and numerical analysis of a far field optical model and proposed a requirement on the wavefront distortion of the telescope optics for LISA [11,12]. Kenny analyzed the wavefront distortion composed of the first 11 terms of Zernike polynomials, and obtained that only those terms with even noll index are relevant to the measured phase error coupling to the beam alignment [13].…”
Section: Introductionmentioning
confidence: 99%